PENILAIAN TERJEMAHAN LAGU BOKUTACHI CHIKYUUJIN SEBAGAI ENDING ANIMASI DORAEMON - Nela Naila Nidhafar; Yenny Aristia Nst; Arza Aibonotika (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This research is a qualitative research method regarding theassessment of Bokutachi Chikyuujin as an opening song of Doraemon animation. Thepurpose of the study is to explain and find out how to objectively assess the translationof Bokutachi Chikyuujin song from Doraemon animation and find out how well thetranslations of the song is based on Newmark's assessment. According to Newmark, theassessment of translation is divided into four categories, including: 1) translation as ascience; 2) translation as a craft; 3) translation as art; and translation as taste. It wasfound that the translation category for the song Bokutachi Chikyuujin’s translation’sscore is 66.5, which went to the translation category B ( good).Key Words: song, translation, assessment.